Parasitic Infections of the Nervous System - Garcia, Hector H.; Nath, Avindra; Del Brutto, Oscar H. (Seminars in Neurology, 2019)
Parasitic infections of the central nervous system are much more common than suspected, although most infections are asymptomatic. For example, parasites like the ubiquitous protozoa Toxoplasma gondii or the nematode larvae Toxocara canis infect significant proportions of the human population. Other parasitic infections such as malaria and neurocysticercosis are widespread in developing countries and become major causes of neurological morbidity in these regions as well in immigrants and travelers. This article reviews parasitic pathogens causing neurological morbidity and mortality, including an extensive list of less common parasitic infections of the human nervous system.
Keywords: parasitic infections; nervous system; malaria; cysticercosis; toxoplasmosis; toxocariasis